SIFAT FISIK DAN KEKUATAN MEKANIK KAYU AKASIA MANGIUM (Acacia mangium Willd) DARI HUTAN TANAMAN INDUSTRI KALIMANTAN SELATAN - Arsad, Effendi (Jurnal Riset Industri Hasil Hutan, 2011)
Acacia Mangium wood can to used for substitution comercial wood. Materiel Acacia mangium woodsÂ  was take from HTI atÂ  seven age with diameterÂ Â  30 â 33 cm.Â  Â The results Physical properties and mechanical strength obtained by the water content of dry air from 13.78 to 14.89%; density of 0.60 to 0.62 gr/cm3; specific gravity of 0.59 to 0.61; compressive strength parallel fibers from 319.54 to 361.70 Kg/cm2; compressive strength perpendicular to fiber 117-197 kg/cm2; bending strength (MOR) from 509.25 to 680.50 kg/cm2; cleave strength 80.25 to 110.90 kg/cm2; tensile strength of 98.27 to Â 133.03 kg/cm2; shear strength of parallel fiber from 93.53 to 149.43 kg/cm2 and hardness from 453 to 565 kg/cm2. Â Physical properties and mechanicalÂ  strenghtÂ  can wasÂ  standardÂ  for furniture andÂ  construction.Keywords: acacia mangium wood, physicalÂ  and mechanicalÂ  wood